Konsep Kafa’ah dalam Membentuk Rumah Tangga Ideal - Efendy, Noor (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Marriage is sunnatullah general and applies to all His creatures, whether in humans, animals and plants, and a way chosen by God as a way for His creatures to breed and preserve his life. Marriage will play after each pair is ready to do a positive role in realizing the goal of marriage it self. Included in terms kafa'ah. In the process of determining a partner, it is recommended to choose one who agrees, is balanced, is equal and is equal. Although this is not a requirement, it is intended to produce harmony in order to avoid reproach. Because often the failure to build a household is caused by striking differences, both differences in religion and in social strata. The husband and wife should be able to actualize in building domestic harmony, in order to reach a destination wedding is sakinah, mawaddah wa rahmah.